2018
DOI: 10.1111/1750-3841.14032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Hydrostatic Pressure on the Shelling Efficacy, Physicochemical Properties, and Microstructure of Fresh Razor Clam (Sinonovacula constricta)

Abstract: High hydrostatic pressure (HHP) is now well known as a nonthermal processing technology and becoming increasingly acknowledged. However, it has not been widely applied to shell seafood due to its uncertain influence on its quality and shelling property. This study could provide valuable information regarding the shelling efficacy, physicochemical properties, and microstructure of razor clam treated by HHP. And it demonstrated that HHP showed a positive impact on quality of razor clam treated by HHP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 57 publications
(80 reference statements)
8
20
0
Order By: Relevance
“…). Similar findings were previously observed in razor clam and silver carp (Qiu et al , ; Xuan et al , ). It is possible that HP can damage the tertiary structure of MP, thus causing the protein to denature and become insoluble (Cruz‐Romero et al , ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…). Similar findings were previously observed in razor clam and silver carp (Qiu et al , ; Xuan et al , ). It is possible that HP can damage the tertiary structure of MP, thus causing the protein to denature and become insoluble (Cruz‐Romero et al , ).…”
Section: Resultssupporting
confidence: 91%
“…The changes of Ca 2+ ‐ATPase activity can indicate that the effects of HP treatment may involve causing protein aggregation or conformational changes. Xuan et al () have reported that Ca 2+ ‐ATPase activity of MP from razor clam treated with 200 to 400 MPa pressure for 1 to 10 min was significantly reduced compared with the untreated group. Torrezan et al () have suggested that enzyme inactivation induced by HP, especially by HP of up to 300 MPa, may be due to the damage to protein structure, resulting in conformational changes.…”
Section: Resultsmentioning
confidence: 99%
“…The drip loss in Group D increased significantly ( p < .05). The results were similar to those reported by Xuan et al (); in that work, the drip loss was rich in protein and water‐soluble nutrients, which promoted bacterial growth in closed packages.…”
Section: Resultssupporting
confidence: 91%
“…Ko et al () noted that the Ca 2+ ‐ATPase in tilapia myosin was susceptible to pressure; the activities declined dramatically when treated ≥100 MPa and remained only 43%, 35%, and 21% by 100, 150, and 200 MPa treatment for 10 min, respectively. Our previous study also showed the adverse effects of pressure on the activity of Ca 2+ ‐ATPase of razor clam (Xuan et al, ). In this study, approximately 53.21%, 37.02%, and 17.11% activity remained after HPAT at 100, 150, and 200 MPa, respectively.…”
Section: Resultsmentioning
confidence: 65%
“…A slight increase in TBARS values was observed in all HPAT‐treated samples, but no significant change was recorded when compared with the fresh one, which was in accordance with the findings obtained with cod muscle (Angsupanich & Ledward, ). However, studies have also been reported that lipid oxidation was accelerated in many aquatic products, including black tiger shrimp, salmon, and razor clam after pressurization (Arnaud et al, ; Kaur, Rao, & Nema, ; Xuan et al, ), indicating that effects of HHP on lipid oxidation of muscles varied vastly on the species, type of muscles, applied pressure level and holding time.…”
Section: Resultsmentioning
confidence: 99%